PERJALANAN REFORMA AGRARIA BAGIAN DARI AMANAH KONSTITUSI NEGARA - Utomo, Setiyo (Veritas et Justitia, 2021)
The author examines and describes how agrarian reform is realized during different government periods. To do that, policy, and legal documents, directly or indirectly related to agrarian reform, is analysed. This research reveals that attempt at agrarian reform up to present is focussed developing policies aiming to restructure land ownership and utilization (land reform).   Another finding is that the promulgation of Law No. 11 of 2020 (Law on Job Creation) tends to shift the focus more on granting easy access to land for development purposes. This change of policy priority will have dire consequence to access to land for the poor and most likely increase agrarian conflicts.